Teaching Evidence-Based Writing : Texts and Lessons for Spot-On Writing About Reading. - Blauman, Leslie A. (Corwin literacy., 2016)
One in a million. Yes, that's how rare it is to have so many write-about-reading strategies so beautifully put to use. Each year Leslie Blauman guides her students to become highly skilled at supporting their thinking about texts, and in Evidence-Based Writing: Fiction, she shares her win-win process. Leslie combed the ELA standards and all her favorite books and built a lesson structure you can use in two ways: with an entire text or with just the excerpts she's included in the book. Addressing Evidence, Character, Theme, Point of View, Visuals, Words and Structure, each section includes: Le.